Isodon rugosus as potential source of phytopharmacological agents: A review - Muhammad Muneeb Ahmad (International Journal of Phytomedicine, 2020)
This piece of writing is aimed to attract the concern of readers and researchers toward the natural bioactive compounds hidden in the depth of natural life. Plant based bioactive compounds have become first choice as a potential source of pharmacological agents. Families of bioactive compounds such as flavonoids, polyphenols, carotenoids, diterpenes, sterols and vitamins enlist the class of naturally occurring families of organic compounds that are widely utilized for the maintenance of natural life. Isodon rugosus is one of the richest plants of Lamiaceae family which contain plenty of biological active compounds. In this review we will focus on labeling and exploring the biological importance of Isodon rugosus. Isodon rugosus plays meaningful role by performing biological activities such as antibacterial, antioxidant, antifungal, anticancer, insecticidal, analgesic and ethnobotanical activities. The strong bioactive potential of Isodon rugosus may act as a key factor to researchers for doing further research work on entire plant to introduce it in pharmacological agents to make the life more sustainable.